A one‐stage sono‐coprecipitation synthesis of porous Fe3O4/bentonite nanocomposite as an adsorbent for methylene blue removal in water. (26th October 2022) - Linh, Ha Xuan; Trung, Nguyen Thanh; Van Thanh, Dang; Huy, Nguyen Nhat; Dung, Nguyen Quoc; Toan, Tran Quoc; Mai, Nguyen Thi; Thuy, Nguyen Thi; Khai, Nguyen Manh
Abstract: A porous Fe3 O4 /bentonite nanocomposite (FBC) was successfully synthesized via an efficient and green co‐precipitation reaction under ultrasonic assistance. The FBC material was characterized by XRD, BET, FTIR and SEM and employed for removing methylene blue from the aqueous solution. The results showed that this nanocomposite owned a reasonably high BET surface area of 98.36 m 2 /g and pore size of 9.32 nm. Adsorption isotherms were also studied for FBC material and methylene blue adsorption isotherm fitted well to Langmuir model with maximum adsorption capacity of 181.82 mg/g. The n value of Freundlich isotherm was 14.45 which indicated physical nature of the adsorption process. It demonstrated the great potential of the material in pollutants adsorption in water and wastewater treatment. Abstract :